2008
DOI: 10.1177/0748730407313364
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Induction of Diapause Requires Regulated Transcription oftimelessin the Larval Brain ofChymomyza costata

Abstract: Photoperiodic signal stimulates induction of larval diapause in Chymomyza costata. Larvae of NPD strain (npd-mutants) do not respond to photoperiod. Our previous results indicated that the locus npd could code for the timeless gene and its product might represent a molecular link between circadian and photoperiodic clock systems. Here we present results of tim mRNA (real time-PCR) and TIM protein (immunohistochemistry) analyses in the larval brain. TIM protein was localized in 2 neurons of each brain hemispher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…In C. costata, clear daily oscillations in tim transcription were observed in the third instar larvae under short-day conditions. Daily tim oscillations were less apparent under long-day conditions, whereas a gradual increase in tim transcript abundance appeared to be the prevailing trend (Stehlík et al 2008). In S. crassipalpis, tim mRNA expression was dampened under long-day conditions (Goto and Denlinger 2002).…”
Section: Expression Patterns Of Per and Timmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. costata, clear daily oscillations in tim transcription were observed in the third instar larvae under short-day conditions. Daily tim oscillations were less apparent under long-day conditions, whereas a gradual increase in tim transcript abundance appeared to be the prevailing trend (Stehlík et al 2008). In S. crassipalpis, tim mRNA expression was dampened under long-day conditions (Goto and Denlinger 2002).…”
Section: Expression Patterns Of Per and Timmentioning
confidence: 99%
“…However, the critical day length of per 0 is obviously shifted as compared with the wild-type (Saunders et al 1989). Another drosophilid fly, Chymomyza costata, a non-photoperiodic-diapause (npd) strain that does not respond to photoperiod, shows lower levels of tim transcripts and TIM abundance in the larval brain than the wild-type (Riihimaa and Kimura 1988;Stehlík et al 2008). In the flesh fly, Sarcophaga bullata, nondiapause phenotype in pupae and arrhythmicity in eclosion are correlated in a variant strain, and the variant strain has higher levels of per and tim expression than the wild-type (Goto et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…In a non-photoperiodic-diapause (NPD) strain of C. costata, of which a single autosomal gene locus encoding tim was mutated, both circadian eclosion rhythms and photoperiodic control of larval diapause were lost (Pavelka et al, 2003). Analysis of tim mRNA and TIM protein in the larval brain indicated that regulated transcription of tim in two brain neurons was required for photoperiodic induction of diapause in C. costata (Stehlik et al, 2008). Studies on D. melanogaster have suggested that tim directly affects the incidence of diapause through circadian photoreception Sandrelli et al, 2007).…”
Section: A Plausible Involvement Of S-ln V S In Photoperiodismmentioning
confidence: 99%
“…Genetic variation in timeless associates with propensity to enter photoperiodically induced diapause in the drosophilids D. melanogaster (Tauber et al, 2007) and Chymomyza costata (Stehlik et al, 2008), and variation in period similarly associates with propensity to diapause in the flesh fly Sarcophaga bullata (Han and Denlinger, 2009). Several gene expression and knockout studies also implicate circadian rhythm genes as potential diapause regulators, although whether the entire pathway is involved remains unresolved (Schiesari et al, 2010).…”
Section: Additional Regulators Of Metabolism and Developmentmentioning
confidence: 99%